Characterization of people with hemato-oncological diseases admitted to an emergency unit - Jéssica Luíza Beck; Silvana Bastos Cogo; Thaís Dresch Eberhardt; Ariele Priebe Reisdorfer; Tais Falcão Gomes; Nara Marilene Oliveira Girardon Perlini
Abstract Objectives: To identify the demographic and clinical profile and the reasons for seeking care of people with hemato-oncological diseases attended at an emergency unit. Methods: This descriptive, correlational, quantitative study was carried in the emergency unit of a general teaching hospital in the state of Rio Grande do Sul, with a sample of 65 patients with hemato-oncological diseases. Simple descriptive statistics were used for the evaluation of the data. Results: There was a predominance of males (61.5%), with a mean age of 63.4 ± 1.7 years, of white skin color (95.4%), with incomplete elementary education (55.4%) and married (53.8%). There was a high rate of patients with cancer receiving end-of-life care (52.3%), a prevalence of palliative care (55.4%), with the outcome most observed being discharge from the unit (52.3%). According to the primary site of the cancer, a predominance of lymphomas and leukemias was observed (30.8%). Regarding the reason for attending the unit, pain (41.5%) was the most prevalent symptom. Conclusion and implications for practice: Identifying these characteristics can contribute to nursing care for patients with hemato-oncological diseases, considering the specificity of this care and the care practice in emergency units.